Retrieving Transmediality. Il gioco di specchi tra avanguardie artistiche e comics - Brancato, Sergio; Pastore, Sara (Mediascapes Journal, 2019)
Transmedia dynamics define the media system by continuously deconstructing and reconstructing its boundaries in an ongoing evolution. Grasping transmediality phenomena prior to the digital revolution is therefore an essential exercise in order to comprehend how contamination and overlapping are structural elements in the mediatic ecosystem. No matter how apparently distant, the intersection between the comics universe and avant-garde visual art is a perfect case study. By analysing the three different but complementary spheres of the aesthetics, the relationship with the institution and the communication with the public, it becomes possible to pick up the signals of the match between avant-garde visual art and comics. The observation of the aesthetic forms shows the stylistic and expressive affinity between these two languages, which denotes a relation of mutual attention and reciprocity. By analysing the relationship with the institution, which constitutes itself as productively and strategically conflictual, is it possible to point out similar goals and tactics. Lastly, the relationship and the communication with the public becomes an exemplary element in showing the substantial changes in the media industry, in the conception of artistic activity and in fruition mechanisms. In light of media landscape’s most recent developing, which follows and at the same time affects in a sort of virtuous circle the technological, economical, political and cultural changes of the social sphere, the analysed fields result again in a relationship of reciprocity, rising both as symptom and outcome of transmediality.